Nonlinear Electronics 1 Nonlinear Dipoles, Harmonic Oscillators and Switching Circuits - Haraoubia, Brahim; Haraoubia, Brahim (ISTE Press - Elsevier, 2018)
Nonlinear Electronics 1: Nonlinear Dipoles, Harmonic Oscillators and Switching Circuits deals with the appearance of nonlinear electronic circuits and their behavior. The book studies a number of circuits that interface between analog and digital electronics, including astable, monostable, bistable, Schmitt trigger, and analog-to-digital and digital-to-analog conversion. Users will find a complete resource that deals with all aspects of these circuits, starting from the discrete component and gradually working to the integrated circuit. - Presents non-linear electronic circuits and their behavior - Discusses relaxation oscillators - Treats subject matter from the discrete element, to the integrated device - Present interface circuits, analog-to-digital conversion, analog-to-analog, and PLL (phase locked loop)